2019
DOI: 10.6018/cpd.347331
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Need Satisfaction and Frustration in Portuguese Exercise Instructors: scale validity, reliabity and invariance between gender

Abstract: Objective: The aim of the present study was to validate the Basic Psychological Need Satisfaction and Frustration Scale in Exercise for fitness instructors. Methods: Data from 477 exercise professionals (319 males, 158 females) was collected. Results: CFA supported the adapted and validated six-factor model: [χ2(237) = 1096.796, χ2/df= 4.63; B-S p < .001, CFI = .930, TLI = .918, SRMR= .0366, RMSEA = .079 (CI90% = .069, .089)], assessing satisfaction and frustration of basic psychological needs in Portuguese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 3 publications
0
7
0
2
Order By: Relevance
“…In present study, this scale showed acceptable fit to the data (see Table 1) as well as acceptable internal consistency (>.73). Previous studies (e.g., Rodrigues et al 2019), supported the validity and reliability of this scale assessing fitness professionals' BPN satisfaction and frustration.…”
Section: Basic Psychological Need Satisfaction and Frustrationmentioning
confidence: 56%
See 1 more Smart Citation
“…In present study, this scale showed acceptable fit to the data (see Table 1) as well as acceptable internal consistency (>.73). Previous studies (e.g., Rodrigues et al 2019), supported the validity and reliability of this scale assessing fitness professionals' BPN satisfaction and frustration.…”
Section: Basic Psychological Need Satisfaction and Frustrationmentioning
confidence: 56%
“…Exercise physiologists completed the Basic Psychological Need Satisfaction and Frustration Scale for exercise physiologists (BPNSFS; Rodrigues et al 2019). This 24-item scale consists of six subscales (4 items each) and was validated specifically for fitness professionals regarding their BPN when prescribing exercise, measuring autonomy (item 7: "When I prescribe exercise I feel a sense of choice and autonomy"), competence (item 12: "When I program exercise trainings I feel confident that I can do them right"), and relatedness (item 9: "When I train clients I feel connected with them") satisfaction, as well as autonomy (item 2: "When I train my clients I feel forced to do exercise sessions I would not choose to do"), competence (item 19: "When I train clients I feel disappointed with my performance"), and relatedness (item 6: "When I prescribe exercise sessions I feel that the relationships I have with gym clients are just superficial") frustration.…”
Section: Basic Psychological Need Satisfaction and Frustrationmentioning
confidence: 99%
“…Concerning the assessment of the variables under analysis, the Basic Psychological Needs Satisfaction and Frustration Scale for exercise instructors was used to assesses how fitness trainers experience needs satisfaction and needs frustration at work. 12 Participants responded to the items using a 5-point scale ranging from 1 ("totally disagree") to 5 ("totally agree"). Composite scores for needs satisfaction and needs frustration was done according to previous assumptions.…”
Section: Methodsmentioning
confidence: 99%
“…Concluindo, após apresentação, análise e discussão dos resultados, é importante refletir sobre a importância do presente trabalho. A análise da frequência dos praticantes de exercício físico em ginásio e health club irá permitir, por exemplo aos gestores e diretores técnicos de um operador fitness, ter indicações acerca do trabalho desenvolvido pelos instrutores de fitness e intervir de forma a melhorar os indicadores de qualidade como forma de melhorar as componentes técnicas destes profissionais na retenção dos utilizadores (Teixeira et al, 2020); ou aos instrutores, retificar e/ou orientar a sua intervenção profissional de acordo com a perceção dos seus praticantes, adequando a prescrição de acordo com as necessidades dos mesmos, dado os comportamentos interpessoais por parte dos instrutores desempenharem um papel crucial (Rodrigues et al, 2019c). Estes exemplos remetem-nos para o problema inicialmente apresentado, focado na necessidade de os ginásios implementarem estratégias para diminuição do abandono e/ou aumento da prática de exercício físico regular a longo prazo (Rodrigues et al, 2020b).…”
Section: Conclusãounclassified